Monetary policies and full employment - Fellner, William John (Hamden, Conn., Archon Books, 1966)
This book is mainly concerned with the bearing of monetary policies on the problem of full employment. It also considered some proposition such as the equilibrium approach; the analytical framework of the Keynesian theory; price and wage rigidities among others in solving the problems of employment.
Includes index
Includes bibliographic footnotes
usc 09/10/18
Loans
Keywords: Full employment policies; Monetary policy; Unemployment; Currency question; Economic policy